The genre of nu jazz: defining its characteristics case study: day by jaga jazzist, and shadows by the kilimanjaro darkjazz ensemble / Raja Azwan-Afiq Raja Azlan - Raja Azlan, Raja Azwan-Afiq (2010)
Musical development throughout the history has generated the creativity of many new artists and musicians. The styles and genres that have been created over the past years quickly evolved into countless other sub-genres making an impossible classification to each one of them. The numerous combinations, mixtures, and fusion of different musical elements add more indistinctiveness to these new sub-genres. Musical style such as Industrial and Intelligent Dance Music or IDM in the Electronic Music subcategory, Post Progressive, Technical Metal and even Avant-garde Metal in the Rock subcategory, as well as Trip Hop in the Hip Hop and R&B subcategory are all musical experimentations without clear explanation or extensive study. In the late 1990's, a new sub category which is known today as Nu Jazz was introduced. This particular sub-genre is said to be a combination of jazz with elements of mostly danceable styles particularly Electronica. Originated from the United States, it is popularized mostly in the European countries such as Norway and the Netherlands. Nu Jazz has now spread widely throughout the world. The vast sound and concept of Nu Jazz may vary greatly from artist to artist making a true definition with regards to its form and structure, specific jazz harmony and theory, and exact instrumentation for this sub-genre is yet to be determined. Thus, this research dissertation is designed specifically to truly define the characteristics of the Nu Jazz genre. Qualitative method was used in collecting data such as books and literature reviews, information from official websites, questions and answers in which the respondents vary from music professors, doctors, composers, and musicians, plus, extensive analysis of full transcriptions on two Nu Jazz's compositions.